ANALISA PENGARUH MOTIVASI KERJA, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWANPT. BANK SYARIAH MANDIRI CABANG JAKARTA THAMRIN - Andi Supianto, - (2014)
Andi Supianto, NRP : 112.092.1171 Influence Analysis of Motivation, Compensation and Workplace toward the Work performance of the employees of PT Bank Syariah Mandiri Jakarta Thamrin Branch. This research aims at finding out the influence motivation , compensation and work environment toward work performance of the employees working fot PT Bank Syariah Mandiri Jakarta Thamrin Branch. Total of personnel working for PT Bank Syariah Mandiri Jakarta Thamrin Branch is 135 persons. By means of Slovin formula, 57 person were selected to be respondents. In this research use statistic method with kuantitatif analysis. In attempt to get primary data, this research used questionnaire model consisting of some statements according to each independent variables. To get quantitative values, the responses of statement were measured with Path analysis. Before distributing the questionnaires, items of statement included in the questionnaires had been examined in accordance with validity and reliability tests. Thus, all items of statements used in the questionnaire were the valid andreliable ones only. Furthermore the primary data was collected from the responses of those 57 persons. The result of this research shows that there is a significant influenceof the variables of work motivation, compensation and work environment toward the work performance among the employees working for PT Bank Syariah Mandiri Jakarta Thamrin Branch either partially or simultaneously. Partially, variable of compensation indicates the highest influence toward variable of work performance with R2 = 0378. Meanwhile, simultaneously the three independent variables determine the highestinfluence toward variable of work performance with adjusted R2 = 0,542.